Het getuigenis aangaande Jezus een pheumatologische verkenning - Floor, L. (Acta Theologica, 2004)
The issue in this article is to what extent people in this postmodern era can know the real meaning about the nature of Jesus of Nazareth. In his First Epistle John answers three questions concerning this problem. How do we know that Jesus is the Son of God? How are we personally related to this extraordinary truth that Jesus of Nazareth is the Son of God? In what way should this personal relationship enter the life of those who are born again? By explaining the work of the Holy Spirit John indicates that there is a close interaction between the doctrine of Jesus the Son of God and the spiritual life of believers.